A emergência do animalismo : um estudo sobre origens, epistemologias e práticas da libertação animal - Márcio Alexandre Buchholz de Barros (2020)
In the present dissertation we investigate the origins, epistemologies and practices of animal liberation movements, in a historical and sociological perspective. It is certainly a preliminary work, since animal liberation/rights movements are broad as they complicated, embracing diverse theoretical and political positions. First of all, we make a brief analysis of the first animal protection organizations origins that emerged in England. We also analyze how animal protection organizations narratives were relatively diverse in their social origins and political spectra. In particular, the study highlights that part of the anarchist thought tradition has a long-standing concern about the animal locus in contemporary societies, and also how suffragette’s movement, in the late 19th and early 20th centuries, had considerable relevance in the antivivisectionist fights. Then, we point out the connections between transformations in animal liberation movements and the emergence of the so called “new social movements” in the late 1960s and early 1970s, when autonomous and countercultural movements context – also close to anarchism – had strong affinity with the animal defense. These movements launch important sociotechnical controversies the question both the moral and ontological status of non-human animals and act to make public, through their actions, debates about instrumental use of animals. The appearance of a more accurate theoretical scope, from the mid-1970s, especially through ethical and deontological philosophers, in addition to feminist epistemologies, worked on the theoretical and practical densification of animal liberation movements. Finally, we analyze the Animal Studies field affirmation, which was given, among other reasons, by the growing criticism of anthropocentric conceptions in the sciences scenario. We point out how this field later unfolds into an academic-active field through clinical studies, and how decolonial prospects have a important implications for animal liberation. Finally, focusing not only on Eurocentric positions, we analyze for animal liberation perception through data collected in three interviews conducted with Latin-American researchers who are close to the theme.